(untitled) (Journal of the College of Education for Women, 2019)
AbstractThis research deals with studying and analysis of a poetic group under thetitle (Trees behind fence) of the great poet Dr. Ahmed Sulaiman AlAhmedwho is the some of the Shek , Sulaiman Al-Ahmed who is the linguist - poetand famous jurist member in the Arabic scientific assemble in Damascus andbrother of the great poet Badawi Al-Jabal. This poetic group include two bigpoetic legends : the first one is (Trees behind fence , ) which include onehundred and eighty four line and the second one ( AZ-Mebadia ) which isconsists of one hundred and seventy eight line, both of them from the (Al-Camil ) meter which is free rhyme which bears a many meaning and picturesand just the great poet composite their poet from it This research depends instudying on mixture between languages systems and it dimensions and theskill of Arts and its branches and the ability of poet on making structure alivingpretty formations which make the listener or the reader stand amazing infront this great talent which used by this poet who updated by pictures andstyles . So, this study was an entrance to go in to the skills of this talent ,which is distributed according to the following items:· Brief statements of the poet’s live .· Introduction.· Research pivot .A- : Semantic:; this point deals with1. Semantic tolerate . 2. Pronounce synonymous3. Arabici ationB- Linguistic extending· Conclusion and results:The phenomena which can not examined and devisal them from the poetry ofthis poet do not be breach as to be literature skills and extending in using newlinguistic context we wish that we have succeeding opening a space lightingthe way in front of instructors to take care in this great character .